Nitric oxide‐releasing microparticles as a potent antimicrobial therapeutic against chronic rhinosinusitis bacterial isolates. Issue 10 (25th July 2018) - Abuzeid, Waleed M.; Girish, Vallerinteavide Mavelli; Fastenberg, Judd H.; Draganski, Andrew R.; Lee, Andrew Y.; Nosanchuk, Joshua D.; Friedman, Joel M.
Abstract : Background: Bacteria, particularly in the biofilm state, may be implicated in the pathogenesis of chronic rhinosinusitis (CRS) and enhance antibiotic resistance. Nitric oxide (NO) is a gaseous immunomodulator with antimicrobial activity and a short half‐life, complicating achievement of therapeutic concentrations. We hypothesized that a novel microparticle‐based delivery platform, which allows for adjustable release of NO, could exhibit potent antibacterial effects. Methods: Porous organosilica microparticles (SNO‐MP) containing nitrosylated thiol groups were formulated. Dissociation of the nitrosothiol groups generates NO at body temperature. The susceptibility of bacterial isolates from CRS patients to SNO‐MP was evaluated through a colony forming unit (CFU) assay. Serial dilutions of SNO‐MP in triplicate were incubated with isolates in suspension for 6 hours followed by plating on tryptic soy agar and overnight incubation followed by CFU quantification. Statistical analysis was performed with SPSS using one‐way analysis of variance with Bonferroni correction. Results: SNO‐MP displayed antibacterial activity against gram‐positive (methicillin‐resistant and ‐sensitive Staphylococcus aureus ) and gram‐negative ( Pseudomonas aeruginosa, Enterobacter aerogenes, and Proteus mirabilis ) isolates. SNO‐MP induced dose‐dependent reductions in CFU across all strains. Compared with controls and blank nanoparticles, SNO‐MP (10 mg/mL) induced a 99.99%‐100% reduction in CFU across all isolates, equivalent to a 5–9 log kill ( p < 0.005). There was no statistically significant difference in CFU concentration between controls and blank microparticles. Conclusion: SNO‐MP demonstrates potent bactericidal effect against antibiotic‐resistant CRS bacterial strains.